Հայկական մշակութային եղեռնը Օսմանյան Թուրքիայի տարածքում - Մերի Քեշիշյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Национальное своеобразие любого народа выражается в его культуре. Каждый, раскрывающий прошлое архитектурный памятник-это говорящий свидетель армянской истории. Уничтожение армянских историко-архитектурных памятников и других культурных ценностей в Западной Армении является составной частью Геноцида армян. Each nation is expressing its national selfness in its culture. Every historical monument even ruined is the stable witness to the Armenian history. The destruction of Armenian historical architectural monuments and other cultural values (churches, gravetombs, memorials, castles etc.) situated on the territory of Western Armenia was component part of policy of Armenian Genocide.
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)